Silver thaw : a Mystic Creek novel - Anderson, Catherine (Adeline Catherine) (Thorndike, Maine : Center Point Large Print, 2015)
"Jeb is annoyed and then intrigued by little strips of paper he finds scattered across his land containing the secret yearnings of Amanda, who has recently moved to Mystic Creek, Oregon, with her six-year-old daughter to escape an abusive husband. Jeb is determined to do anything to make her yearnings come true"--
Keywords: Large type books; Love stories